Intelligent meters for improved system operation and customer relationship management - Fung, C.C.; Wong, K.P.; Wong, K.W.; Goh, Ong Sing; Law, T. (IEEE, 2002)
Since the time. that electric power meters were introduced in the 1870s, the basic function of the meters has remained more or less unchanged. Many developed countries are still using the same technology that has existed for more than a century. In particular, meter readings for residential services are normally taken manually once a month or every two months. While automatic meter reading (AMR) has gradually been introduced in many places, the cost involves in retrofitting the existing systems may not be justified if they are used merely for meter reading. This paper proposes two approaches to enhance the functions of the meters intelligently thereby improving the operation of the electrical supply system and customer relationship management. Data mining (DM) techniques are first discussed for information extraction and an intelligent agent (IA) technique is also proposed for front-end customer services.